The teacher of Warsaw : a novel - Escobar, Mario, 1971- (Harper Muse, an imprint of Harper Collins Focus LLC, 2022)
"International bestselling author Mario Escobar captures the strength of the human spirit and the enduring power of kindness in this moving novel based on the true story of a brave Polish teacher who cared for hundreds of orphans in the Warsaw Ghetto"--